Pandemic Worry and Preventive Health Behaviors During the COVID-19 Outbreak - Li, Minghui; Lv, Gang; Hsieh, Stephanie; Shao, Rongjie; Yuan, Jing (Frontiers in Medicine, 2021)
Objective: As schools are preparing for onsite learning, it is urgently needed to characterize the extent of pandemic worry and to examine predictors of adopting preventive health behaviors of hand washing, face mask wearing, and maintaining social distance among student pharmacists. Methods: An online survey was sent to 326 student pharmacists in the United States. Pandemic worry was measured using a seven-point Likert scale ranging from extremely not afraid of, to extremely afraid of getting COVID-19. The health belief model (HBM) was the theoretical framework of this study. Preventive health behaviors and components of the HBM were also measured using seven-point Likert scales (one indicated extremely unlikely; seven indicated extremely likely). Multivariable linear regression models were used to identify predictors of each behavior. Results: A medium level of pandemic worry (M = 4.2, SD = 1.92) was identified and females reported a higher pandemic worry. Respondents reported that they were extremely likely to wash their hands (M = 6.8, SD = 0.48) and maintain social distance (M = 6.6, SD = 0.92), but were moderately unlikely to wear face masks (M = 2.2, SD = 1.51). Determinants of face mask wearing included pandemic worry, perceived benefits, cue to action, self-efficacy, and being of an Asian American. Perceived barriers were negatively associated with face mask wearing. Conclusion: Strategies should be implemented to reduce the psychological impact of COVID-19 pandemic among student pharmacists. Predictors identified in this study should be incorporated in efforts to improve face mask wearing. Continued monitoring of pandemic worry and preventive health behaviors is of great significance when universities and colleges are for onsite learning.